PENGEMBANGAN LEMBAR KERJA PESERTA DIDIK (LKPD) BERBASIS RECIPROCAL TEACHING PADA MATERI BANGUN RUANG SISI DATAR KELAS VIII MTsN 2 KOTA PARIAMAN - Sekar Prima Putri; Martin Kustati; Nita Putri Utami (UIN Imam Bonjol Padang, 2022)
This research is a development research that aims to produce valid and practical mathematical worksheets based on Reciprocal Teaching. The research subjects were students of class VIII MTsN 2 Kota Pariaman. This research was carried out using a 4-D model consisting of 4 stages, namely defining, designing, developing and disseminating. In this research, it is limited to the development stage. The definition stage consists of syllabus analysis, literature analysis, concept analysis, formulation of learning objectives, analysis of educators and students. At the design stage, the LKPD based on Reciprocal Teaching is designed and the LKPD assessment instrument is drafted. At the development stage, the LKPD validity test and LKPD practicality test were carried out. The LKPD validity test was carried out by five experts, namely 3 mathematicians, 1 Indonesian language expert, 1 educational technology expert. The practicality test on the LKPD is seen from the practicality questionnaire and the results of interviews with educators and students. The results showed that the Student Worksheet (LKPD) based on Reciprocal Teaching met the valid criteria with an average validity of 81.8% and met the very practical criteria with an average practicality of 89% by educators and met the very practical criteria with an average practicality. 86.75% by students. In general, the LKPD based on Reciprocal Teaching is valid and practical to use in learning mathematics in Building a Flat Sided Space.